The Role of the Pharmacist in the Care of Patients with Chronic Pain - Murphy L; Ng K; Isaac P; Swidrovich J; Zhang M; Sproule BA (Dove Medical Press, 2021)
Laura Murphy,1 Karen Ng,2 Pearl Isaac,3 Jaris Swidrovich,4 Maria Zhang,3,5 Beth A Sproule3,5 1Department of Pharmacy, University Health Network, Toronto, ON, Canada; 2Toronto Academic Pain Medicine Institute, Toronto, ON, Canada; 3Pharmacy Department, Centre for Addiction and Mental Health, Toronto, ON, Canada; 4College of Pharmacy and Nutrition, University of Saskatchewan, Saskatoon, SK, Canada; 5Leslie Dan Faculty of Pharmacy, University of Toronto, Toronto, ON, CanadaCorrespondence: Beth A SprouleCentre for Addiction and Mental Health (CAMH), 1025 Queen Street West, Toronto, ON, M6J 1H4, CanadaTel +1-416-535-8501 x35601Fax +1-416-583-1277Email beth.sproule@camh.caAbstract: Pharmacists across the healthcare continuum are well positioned to collaborate with patients to effectively manage their chronic pain. Evidence supports positive outcomes when pharmacists undertake these roles; however, there are barriers preventing uptake across the profession. This paper aims to expand awareness of the breadth of these roles, including pharmaceutical care provision, interprofessional collaboration, pain and medication education, support for patients in self-management and acceptance of responsibility to be culturally responsive and decrease stigma. Pharmacists are accessible healthcare professionals and can improve the care of patients with chronic pain.Keywords: chronic pain, pharmacist, patient-centered care, stigma